Munchausen Syndrome. Issue 4 (April 2020) - Prabhu, Angeline; Abaid, Bilal; Sarai, Simrat; Sumner, Riley; Lippmann, Steven
Abstract : Abstract: Munchausen syndrome is a factitious disorder that is difficult to diagnose and treat. This article clarifies points for clinical recognition and management of patients with this condition. Patients with this condition often are dramatic and provide false and/or exaggerated symptoms or information. They solicit attention from physicians, going doctor-to-doctor, having repeated diagnostic tests, procedures, hospitalizations, and evidence little improvement. Adherence to treatment plans is generally suboptimal and the patients frequently leave the hospital against medical advice. A compassionate, multidisciplinary approach to treatment is advised. It often includes conjoint clinical communication between the primary care physician and a psychiatrist. Open, supportive discussion with the patient about his or her condition is important. Long-term psychotherapy and follow-up are recommended. Abstract : Munchausen syndrome is a serious factitious disorder presenting mostly in men. Early diagnostic recognition of patients with Munchausen syndrome is important to improve medical care and maintain quality of life. The patients present in a confusing pattern, and this review aims to enhance early identification of such symptomology as an aid to diagnostic skills.